2009
DOI: 10.1161/circulationaha.108.842641
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival of the Very Elderly Undergoing Aortic Valve Surgery

Abstract: Background— Increasing numbers of the very elderly are undergoing aortic valve procedures. We describe the short- and long-term survivorship for this cohort. Methods and Results— We conducted a cohort study of 7584 consecutive patients undergoing open aortic valve surgery without (51.1%; AVR) or with (48.9%; AVR + CABG) concomitant coronary artery bypass graft surgery between November 10, 1987 through June 30, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 33 publications
3
47
1
5
Order By: Relevance
“…The change in life years was estimated as the difference in mortality rate between EIE-FS-RDAVR and FS-AVR multiplied by the life expectancy of the individual. Consistent with a previous analysis, we assumed an average life expectancy of 11 years for surgical AVR individuals in this population [42,43]. The Likosky study, besides finding comparable long-term survivorships between AVR patients and a general population of similar age, also found that this survival varied little and was not contingent on the type of AVR surgery.…”
Section: Incremental Costssupporting
confidence: 71%
See 2 more Smart Citations
“…The change in life years was estimated as the difference in mortality rate between EIE-FS-RDAVR and FS-AVR multiplied by the life expectancy of the individual. Consistent with a previous analysis, we assumed an average life expectancy of 11 years for surgical AVR individuals in this population [42,43]. The Likosky study, besides finding comparable long-term survivorships between AVR patients and a general population of similar age, also found that this survival varied little and was not contingent on the type of AVR surgery.…”
Section: Incremental Costssupporting
confidence: 71%
“…Its prevalence increases with age, from 2.5% at 75 years to 8.1% at 85 years [46]. Left untreated, disease progression is rapid and fatal with a mean survival time of only 1.5-3 years past diagnosis [42]. Elective FS-AVR performed through FS has been deemed a safe procedure since it carries low morbidity and short/long-term mortality rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gulbins et al [18 ]also observed higher mortality rates in patients undergoing AVR/CABG compared to those undergoing either AVR or CABG alone, concluding that the additional risk of mortality was real, but actually lower than that predicted, based on the EuroSCORE. Although combined AVR and CABG does carry with it a significantly higher mortality risk in the immediate postoperative period, this appears primarily related to the increased complexity of the procedure rather than something intrinsic to the patient selection process, as similar preoperative comorbidities and postoperative complications have been present in patients undergoing AVR alone, CABG alone or combined procedures (table 7) [9,17]. …”
Section: Discussionmentioning
confidence: 99%
“…Increasing use of TAVI in older moderate risk patients is based on registry data showing that outcomes of TAVI in moderate risk patients are superior compared to those in high surgical risk patients [3,[16][17][18]. It is also known that surgical outcomes in older patients are worse than in younger patients [19,20]. Recently, a randomised trial Figure 1.…”
Section: Discussionmentioning
confidence: 99%